The influence of childhood socioeconomic status on academic engagement among adolescents: the mediating role of internalization of learning motivation and learning burnout - Zhong, Shuang; Yuan, Guangzhe; Gu, Yanqiu; Liu, Caimeng (Frontiers in Psychology, 2025)
A paucity of studies has hitherto been observed in the field of research concerning the relationship between childhood socioeconomic status (SES) and academic engagement, as well as the potential mechanisms involved. The present study therefore sought to explore the effect of childhood SES on adolescents’ academic engagement, and the underlying mechanisms that may facilitate or hinder this engagement. The study was anchored in the theoretical frameworks of Self-Determination Theory and Life History Theory. A sample of 611 Chinese adolescents (Mage = 16.91, SD = 0.37, 41.2% male) were investigated in the study. The findings indicated that childhood SES had a substantial and positive influence on adolescents’ academic engagement. Furthermore, childhood SES exerts an indirect influence on adolescent academic engagement, manifesting in the internalization of learning motivation and the development of learning burnout. The hypothesis is put forward that an increase in the academic engagement of adolescents can be achieved through the promotion of learning motivation, as well as the alleviation of learning burnout.